PENAWARAN BERAS DI KOTA PADANG - Angelia Leovita; Dian Fauzi (Universitas Teuku Umar, 2018)
Rice is very important for the survival of Indonesian people. Because most of the food from Indonesian society is rice. Problems will arise if the availability of rice is not able to meet the rice needs of the community. The purpose of this study is to analyze the extent to which rice price and harvest area variabels affect rice supply in Padang City. The analytical tool used is Multiple Linear Regression. The results of the study show that both the rice price and harvest area variabels have a significant effect and are positive for the rice supply in Padang City.